Lateral advancement flap for sacrococcygeal pilonidal sinus: reassessment study - Arora, Bhavinder K.; Arora, Rachit; Arora, Akshit (International Surgery Journal, 2017)
Background: Sacrococcygeal pilonidal sinus disease is treated better with various flaps and primary closure. This study was aimed to describe the lateral advancement flap in surgical treatment of sacrococcygeal pilonidal sinus disease in an effort to redefine the results of this technique. It is a fascio-adipo-cutaneous flap which is advanced from one buttock to opposite across the natal cleft and providing the off midline closure with cleft lift. Methods: The results of this technique were assessed in 65 patients. The technique consists of adequate excisions of sinus, tracts and surrounding inflamed tissue till depth of presacral fascia. The defect was covered with a thick lateral advancement flap and produce an off midline closure and cleft lift. Results: The sixty patients were hirsute males and five were hairless females. The maximum length and breadth covered was 7x5cm. The operative time taken was 40±10 minutes. The average hospital stay was 5 to 7 days. The surgical site infection in 4 patients and wound dehiscence occurred in one patient only. No recurrence was recorded in follow up period of one year. Conclusions: The lateral fascio-cutaneous advancement flap is gaining popularity for its ease of designing and harvesting. The short hospital stay, minimum postoperative complications, no recurrence and acceptable aesthetic results make this a uniformly acceptable technique for surgical primary closure of pilonidal sinus disease.